On Deferred Statistical and Strong Deferred Cesàro Convergences of Sequences With Respect to A Modulus Function - Belen, Cemal; Yıldırım, Mustafa (Cumhuriyet Science Journal, 2023)
Let f be any modulus function. We prove that the classes of strongly deferred Cesàro convergent sequences defined by f and deferred statistical convergent sequences are equivalent if the sequence is f-deferred uniformly integrable. Some converse inclusions are obtained when the modulus function f is compatible. Finally, for any compatible modulus f, we prove that any sequence is f-strongly deferred Cesàro convergent if and ony if it is deferred f-statistically convergent and deferred uniformly integrable.